Knowledge, Beliefs and Attitudes towards Herbal Medicine – A Community-based Survey from a Central Region of Saudi Arabia - Al Yousef, Hanan Mohammed; Wajid, Syed; Sales, Ibrahim (Indian Journal of Pharmacy Practice)
Background and Objectives: Herbal products are widely used in many countries in various forms including roots, leaves, barks seeds and so many, for inhibiting and treating Number of minor and major disorders. The purpose of this study was to evaluate the prevalence of self-medication with complementary and alternative medicine (CAM) in capital of Saudi Arabia (SA). Methods: A cross-sectional, descriptive online survey was conducted among general public from February to April 2018 using Google Forms. The survey was divided into 3 themes and comprised of 23 items that gathered information about the attitudes, perceptions and knowledge of respondents toward CAM. Results: Approximately 51 % of the respondents believed that herbal medications (HM) are better than commercially available prescription and over-the-counter drugs. About to 78.2 % believed that going to a physician is better than HM. Over half (53.7 %) reported that their physicians were aware of their CAM use. The most common influences for using this type of treatment were family and friends (68.9 %) followed by the internet (20.3 %). The most commonly reported herbal medicines used are ginger (61 %) and cinnamon (25 %). Nearly half of the respondents (46.5 %) reported that joint pain is the most common ailment for using HM. Conclusion: The study revealed a high prevalence of HM use among general community of KSA. More awareness and education about risks and complications of HM use are needed for both public and healthcare professionals.
Keywords: Knowledge; Beliefs; Attitudes; Herbal medicine; Saudi Arabia.